2004
DOI: 10.1186/bcr958
|View full text |Cite
|
Sign up to set email alerts
|

Membrane estrogen receptor-α levels in MCF-7 breast cancer cells predict cAMP and proliferation responses

Abstract: Introduction 17β-estradiol (E 2 ) can rapidly induce cAMP production, but the conditions under which these cAMP levels are best measured and the signaling pathways responsible for the consequent proliferative effects on breast cancer cells are not fully understood. To help resolve these issues, we compared cAMP mechanistic responses in MCF-7 cell lines selected for low (mER low ) and high (mER high ) expression of the membrane form of estrogen receptor (mER)-α, and thus addressed the receptor subform involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 55 publications
1
86
0
Order By: Relevance
“…Rather our findings suggest that E 2 's effects on mast cell mediator release are through a membrane-associated (non-genomic) form of ER-α. This type of ER stimulation has been shown to induce rapid cellular responses through G-protein activation, (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan et al, 2000;Improta-Brears et al, 1999;Stefano et al, 1999;Watson et al, 1999) which can include various signaling pathways involving Ca 2+ fluxes, and modulation of mitogen-activated protein kinases and adenyl cyclase (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan and Harvey, 2003;Nadal et al, 2000;Song et al, 2004;Zivadinovic et al, 2005). Indeed, we found that intracellular Ca 2+ was increased within the first 2.5 min after estrogenic stimulation of RBL.…”
Section: Discussionmentioning
confidence: 49%
“…Rather our findings suggest that E 2 's effects on mast cell mediator release are through a membrane-associated (non-genomic) form of ER-α. This type of ER stimulation has been shown to induce rapid cellular responses through G-protein activation, (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan et al, 2000;Improta-Brears et al, 1999;Stefano et al, 1999;Watson et al, 1999) which can include various signaling pathways involving Ca 2+ fluxes, and modulation of mitogen-activated protein kinases and adenyl cyclase (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan and Harvey, 2003;Nadal et al, 2000;Song et al, 2004;Zivadinovic et al, 2005). Indeed, we found that intracellular Ca 2+ was increased within the first 2.5 min after estrogenic stimulation of RBL.…”
Section: Discussionmentioning
confidence: 49%
“…In our study, Western blot analyses showed that treatment of the cells with high concentrations of 17h-E induced ERK1/2 activation that was sustained even after 72 h, unlike treatment with lower concentrations of 17h-E, which resulted in an ERK1/2 activation that was not sustained. 17h-E has been shown to activate the mitogen-activated protein kinase pathway in other studies (37) and a constitutive activation of the mitogen-activated protein kinase pathway leads to antiproliferative signals generated to restrict cell proliferation, whereas transient activation may induce proliferation (40,41). Our data suggest that exposure to high levels of 17h-E induces a constitutive activation of ERK1/2, resulting in growth arrest, and that ANXA1 is upstream of ERK1/2 and in turn regulates ERK1/2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our past studies in both a pituitary tumor cell line selected for robust nongenomic estrogenic responses, and similarly selected MCF-7 breast cancer cells, clearly indicate that a membrane version of ERα is involved. We demonstrated this via antibody (Ab)-elicited responses, increased or decreased receptor expression linked to responses, antisense knockdown of ERα, and the absence of other estrogen receptor types in these cells [31][32][33][34][35][36][37][38].…”
Section: The Debate About the Identity Of Steroid Receptor Proteins Tmentioning
confidence: 99%